Plan de Proyecto de Construcción de Subestación Moín #4 Ampliación #9 - Solano-Rodríguez, Rolando (Instituto Tecnológico de Costa Rica, 2005)
This project was done with the purpose of obtaining a Project Plan for the construction of electrical substations, some data were taken as reference for this document from the Moinיs Substation #4 enlargement #9. In this project you can find themes such as: projectיs profile, work breakdown structure, projectיs schedule, personal flow, responsibility matrix, events calendar and complementary management plans. “In each one of these subjects there are methods, procedures and tools used to begin, plan execute, control and close these projects.”1 It was concluded that planning is a fundamental tool for decision making in the area of construction. Without planning, the execution, control and closure transform themselves into a big problem, which will be reflected in the projectיs development. Planning allows also an efficient resource utilization and makes the teamיs position and direction of the project stronger, because it minimizes the negative influences and transfers direct responsibilities to the projectיs team members.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2005.
Keywords: Planificación; Administración de proyectos; Gestión de la integración; Control del tiempo; Mejora continua